MUSIC AS THE SOCIAL AND CULTURES PHENOMENON IN THE CONTEXT OF INFORMATION SPACE - Воронова, Н. С. (Proceedings of the Kyiv Aviation Institute. Series: Philosophy. Cultural, 2015)
Research is dedicated to social philosophy analysis of music as social cultural phenomenon in the context of information space.